Can we breed for durable resistance to broomrapes? - RUBIALES, Diego (Phytopathologia Mediterranea, 2018)
The broomrapes (Orobanche and Phelipanche) are parasitic plants that have modified biology to feed on other plants, completely losing autotrophic capability. Some broomrape species have adapted to agricultural ecosystems becoming parasitic weeds. The most damaging weedy broomrapes are O. crenata, O. foetida, O. minor, O. cumana, O. cernua and P. ramosa and P. aegyptiaca, which can severely constrain important dicotyledonous crops, mainly in the Mediterranean Basin. This adaptation is an active process, with recent instances of jumps from non-weedy to weedy behavior, such as for O. cumana adapting to infect sunflower little more than a century ago; O. cernua adapting to infect tomato, tobacco and eggplant; and the more recent example of O. foetida adapting to infect faba bean a few decades ago. This also relates to parasite speciation towards particular hosts, such as the ongoing process of P. ramosa populations infecting winter oilseed rape. Sunflower is a unique situation, in which highly effective monogenic resistances to broomrape have been identified and widely deployed by sunflower breeders. This was accompanied by the subsequent appearance and spread of new races of O. cumana overcoming the introduced host resistance genes. In contrast, only quantitative resistances were identified and exploited by breeders in other crops against other broomrapes. Achievements and prospects for broomrape resistance breeding are presented and critically discussed, along with complementary measures needed to preserve durability of resistance. Particularly important is the prevention of human-driven broomrape seed dispersal by crop seed trade, together with broomrape seed soil-bank demise.